Long‐term postnatal outcome of fetuses with prenatally suspected septo‐optic dysplasia. (1st September 2020) - Shinar, S.; Blaser, S.; Chitayat, D.; Selvanathan, T.; Chau, V.; Shannon, P.; Agrawal, S.; Ryan, G.; Pruthi, V.; Miller, S. P.; Krishnan, P.; Van Mieghem, T.
ABSTRACT: Objectives: Septo‐optic dysplasia (SOD) is a clinical syndrome characterized by varying combinations of optic nerve hypoplasia, pituitary gland hypoplasia and abnormal cavum septi pellucidi. It is suspected on prenatal imaging when there is non‐visualization or hypoplasia of the septal leaflets. Long‐term postnatal outcomes of fetuses with prenatally suspected SOD have been documented poorly. The aims of this study were to describe the natural history of deficient septal leaflets, to quantify the incidence of postnatally confirmed SOD and to document the visual, endocrine and long‐term neurodevelopmental outcomes of these infants. Methods: This was an observational retrospective study of all fetuses with prenatal imaging showing isolated septal agenesis, assessed at a single tertiary center over an 11‐year period. Pregnancy, delivery and neonatal outcomes and pre‐ and postnatal imaging findings were reviewed. Neonatal evaluations or fetal autopsy reports were assessed for confirmation of SOD. Ophthalmologic, endocrine, genetic and long‐term developmental evaluations were assessed. Imaging findings and outcome were compared between infants with and those without postnatally confirmed SOD. Results: Of 214 fetuses presenting with septal absence on prenatal ultrasound and magnetic resonance imaging (MRI), 18 (8.4%) were classified as having suspected isolated septal agenesis suspicious for SOD. Uniform prenatal MRI findings in cases with suspected SOD included remnants of the leaflets of the cavum septi pellucidi, fused forniceal columns, normal olfactory bulbs and tracts and a normal optic chiasm. Twelve fetuses were liveborn and five (27.8%) had postnatally confirmed SOD. Only two of these five fetuses had additional prenatal imaging features (pituitary cyst, microphthalmia and optic nerve hypoplasia) supporting a diagnosis of SOD. The other three confirmed SOD cases had no predictive prenatal or postnatal imaging findings that reliably differentiated them from cases without confirmed SOD. Visual and endocrine impairments were present in two (40%) and four (80%) cases with confirmed SOD, respectively. In those with visual and/or endocrine impairment, developmental delay (median age at follow‐up, 2.5 (interquartile range, 2.5–7.0) years) was common (80%) and mostly severe. Neonates with isolated septal agenesis and a lack of visual or endocrine abnormalities to confirm SOD had normal development. Conclusions: Only a quarter of fetuses with isolated septal agenesis suggestive of SOD will have postnatal confirmation of the diagnosis. Clinical manifestations of SOD are variable, but neurodevelopmental delay may be more prevalent than thought formerly. © 2020 Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.